2007
DOI: 10.1152/ajpgi.00276.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enteric glia inhibit intestinal epithelial cell proliferation partly through a TGF-β1-dependent pathway

Abstract: Although recent studies have shown that enteric neurons control intestinal barrier function, the role of enteric glial cells (EGCs) in this control remains unknown. Therefore, our goal was to characterize the role of EGCs in the control of intestinal epithelial cell proliferation using an in vivo transgenic and an in vitro coculture model. Assessment of intestinal epithelial cell proliferation after ablation of EGCs in transgenic mice demonstrated a significant increase in crypt cell hyperplasia. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
124
0
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(144 citation statements)
references
References 26 publications
12
124
0
8
Order By: Relevance
“…Similar results were obtained by Wang et al [38] in his study of pigs supplemented with 1 g/kg lactoferrin. Although, the villi in group CL are only slightly longer than villi of group Ci, without statistical significance, this result proves more consistent with the findings from the literature, which clearly demonstrates that there are highly effective mechanisms for maintaining the homeostasis of the intestinal epithelium [28][29][30]. The same is valid, therefore, when comparing the depth of the crypts in these two groups and also, in groups CL and SL, which showed no difference in crypt depth, even though the villus height was significantly higher in group CL.…”
Section: Histomorphometry Of the Intestinal Mucosasupporting
confidence: 90%
See 2 more Smart Citations
“…Similar results were obtained by Wang et al [38] in his study of pigs supplemented with 1 g/kg lactoferrin. Although, the villi in group CL are only slightly longer than villi of group Ci, without statistical significance, this result proves more consistent with the findings from the literature, which clearly demonstrates that there are highly effective mechanisms for maintaining the homeostasis of the intestinal epithelium [28][29][30]. The same is valid, therefore, when comparing the depth of the crypts in these two groups and also, in groups CL and SL, which showed no difference in crypt depth, even though the villus height was significantly higher in group CL.…”
Section: Histomorphometry Of the Intestinal Mucosasupporting
confidence: 90%
“…However, in an experiment using cultures of various strains of intestinal cells, Goke et al [29] demonstrated that differentiated fibroblasts (myofibroblasts) often present in these culture models, regulate cell proliferation by paracrine action. More recently, Neunlist et al [30], also in an in vitro experiment have shown that neuronal and glial components of the enteric nervous system, particularly the glial cells, could act together with other components of the mucosa, such as myofibroblasts, to enhance the control over cell proliferation in the intestinal epithelium and contribute to the maintenance of homeostasis.…”
Section: Weight Of Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Le concept d'UNGE s'est développé récemment sur la base de données anatomiques montrant : -1) l'existence d'une importante innervation de la BEI composée d'axones et de cellules gliales, chaque villus étant innervé par 70-92 neurones sous-muqueux chez le cobaye (Song et al 1995) et -2) la proximité étroite entre les fibres nerveuses et les CEI, séparées uniquement par la lame basale dont l'épaisseur est de l'ordre du micromètre (Neunlist et al 2007 ;Van Landeghem et al 2011).…”
Section: L'unité Neuro-glio-épithéliale Digestive : Ungeunclassified
“…Enfin, les CGE jouent un rôle majeur dans le contrôle de la prolifération des CEI. Ainsi, les CGE inhibent la prolifération des CEI par la libération du transforming growth factor ␤1 (TGF ␤1) ou de la 15-deoxy-12,14-prostaglandine J2 (15dPGJ2) (Neunlist et al 2007 ;Bach-Ngohou et al2010). D'autre part, l'ablation des CGE in vivo conduit à une hyperplasie des cryptes et une hyper-prolifération des CEI.…”
Section: Contrôle Des Fonctions De La Bei Par Les Cellules Gliales Enunclassified